Longshore wind, waves and currents: climate and climate projections at Ninety Mile Beach, southeastern Australia. (24th February 2015) - O'Grady, Julian G.; McInnes, Kathleen L.; Colberg, Frank; Hemer, Mark A.; Babanin, Alexander V.
ABSTRACT: It is shown that Lakes Entrance, a township located at the northern end of Ninety Mile Beach in southeastern Australia, is situated in a region that may experience noticeable changes in longshore wind, wave and ocean currents compared to present day climate variability as a consequence of the southward shifting subtropical ridge (STR) predicted in global climate change models. These changes could modify sediment transport in the littoral zone and impact the coastline position. Thirty‐year hindcasts of winds, coastal currents and waves are shown to agree well with available observations and provide a long‐term dataset of the climate variability. Hindcasts of coastal ocean currents and waves indicate that while the annual net mean wave and current transport are in opposing directions, their seasonal adjusted monthly anomalies are positively correlated. Furthermore they are also correlated with the position of the STR location index. On seasonal to annual time scales a weak connection between the transport variables and Southern Oscillation Index (SOI) is found. It appears that during multiple years of positive (negative) SOI conditions the STR is located north (south) of its mean monthly position, resulting in anomalous eastward (westward) transport. The four climate models used in this study indicate a southward shift in the STR for most months under a high emission future. In summer months the shift in the STR results in both increased summer westward wind‐driven currents and westward wave forcing. Changes in winter months are less related to the STR location and it is discussed that the contraction and increased intensity of the westerly storm belt linked to Southern Annular Mode could possibly influence the transport. The analysis is presented at the coastal scale to provide insights into how these changes may affect net transport across the littoral zone in more detailed numerical nearshore sediment transport modelling.